2022
DOI: 10.1002/lol2.10264
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of planktonic ciliates differs between marine and freshwaters: A case study providing guidance for climate change studies

Abstract: Predicting the performance of aquatic organisms in a future warmer climate depends critically on understanding how current temperature regimes affect the organisms' growth rates. Using a meta‐analysis for the published experimental data, we calculated the activation energy (Ea) to parameterize the thermal sensitivity of marine and freshwater ciliates, major players in marine and freshwater food webs. We hypothesized that their growth rates increase with temperature but that ciliates dwelling in the immense, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Ciliate abundance was highest in spring and summer. Similar observations were reported by Gilbert et al (1998) and by Lukic et al (2022), who showed the highest abundance of ciliates in spring and summer in the aquatic environment [35,86]. According to the literature, ciliates are sensitive to changes in environmental conditions due to their thin cell membrane [87].…”
Section: Effect Of Biogenic Compounds On Testate Amoebae and Ciliatessupporting
confidence: 82%
“…Ciliate abundance was highest in spring and summer. Similar observations were reported by Gilbert et al (1998) and by Lukic et al (2022), who showed the highest abundance of ciliates in spring and summer in the aquatic environment [35,86]. According to the literature, ciliates are sensitive to changes in environmental conditions due to their thin cell membrane [87].…”
Section: Effect Of Biogenic Compounds On Testate Amoebae and Ciliatessupporting
confidence: 82%
“…Exceptions to the general rule that rising temperatures reduce organism size and increase growth rates are known for some small aquatic ectotherms (Atkinson 1995). Lukić et al (2022) concluded that the lack of an allometric relationship between ciliate cell volumes and growth rates results from the relatively narrow size range of the ciliates studied thus far. Yet, this does not apply to the present study and may explain why I found a marginally significant volume effect on δ max .…”
Section: Discussionmentioning
confidence: 99%
“…I found that δ max and r max were significantly correlated but that the latter, in contrast to the former, was unrelated to ciliate cell volume (data not shown). Similarly, a recent analysis of ciliate-specific growth rates reported that r max did not decline with increasing cell volume (Luki c et al 2022). Accordingly, the available data on ciliate mortality rates and specific growth rates provide little support for the tenets of the metabolic theory of ecology that all metabolic rates increase with temperature and scale allometrically with size (Brown et al 2004).…”
Section: Physiological Mortality Vs Predator-induced Mortalitymentioning
confidence: 94%
See 2 more Smart Citations